Bag1 is essential for differentiation and survival of hematopoietic and neuronal cells - Götz, Rudolf; Wiese, Stefan; Takayama, Shinichi; Camarero, Guadalupe C; Rossoll, Wilfried; Schweizer, Ulrich; Troppmair, Jakob; Jablonka, Sibylle; Holtmann, Bettina; Reed, John C; Rapp, Ulf R; Sendtner, Michael (Nature neuroscience, 2005)
Bag1 is a cochaperone for the heat-shock protein Hsp70 that interacts with C-Raf, B-Raf, Akt, Bcl-2, steroid hormone receptors and other proteins. Here we use targeted gene disruption in mice to show that Bag1 has an essential role in the survival of differentiating neurons and hematopoietic cells. Cells of the fetal liver and developing nervous system in Bag1 −/− mice underwent massive apoptosis. Lack of Bag1 did not disturb the primary function of Akt or Raf, as phosphorylation of the forkhead transcription factor FKHR and activation of extracellular signal–regulated kinase (Erk)-1/2 were not affected. However, the defect was associated with the disturbance of a tripartite complex formed by Akt, B-Raf and Bag1, in addition to the absence of Bad phosphorylation at Ser136. We also observed reduced expression of members of the inhibitor of apoptosis (IAP) family. Our data show that Bag1 is a physiological mediator of extracellular survival signals linked to the cellular mechanisms that prevent apoptosis in hematopoietic and neuronal progenitor cells.